Lack of anti-inflammatory and anti-catabolic effects on basal inflamed osteoarthritic chondrocytes or synoviocytes by adipose stem cell-conditioned medium. Issue 11 (November 2015) - Manferdini, C.; Maumus, M.; Gabusi, E.; Paolella, F.; Grassi, F.; Jorgensen, C.; Fleury-Cappellesso, S.; Noël, D.; Lisignoli, G.
Summary: Objective: To define whether good manufacturing practice (GMP)-clinical grade adipose stem cell (ASC)-derived conditioned medium (CM) is as effective as GMP-ASC in modulating inflammatory and catabolic factors released by both osteoarthritis (OA) chondrocytes or synoviocytes. Methods: OA chondrocytes and synoviocytes were treated with ASC-CM or co-cultured with ASC. Inflammatory factors (IL6, CXCL1/GROα, CXCL8/IL8, CCL2/MCP-1, CCL3/MIP-1α and CCL5/RANTES) and proteinases, such as metalloproteinase (MMP13), a disintegrin and metalloproteinase with thrombospondin motifs (ADAMTS4, ADAMTS5) and their tissue metalloproteinase inhibitors (TIMP1, TIMP3) were evaluated by qRT-PCR or immunoassays. The involvement of prostaglandin E2 (PGE2) was also analyzed. Results: Most ASC-CM ratios tested did not decrease IL6, CCL2/MCP-1, CCL3/MIP1-α, CCL5/RANTES on basal inflamed chondrocytes or synoviocytes in contrast to what we found using ASC in co-culture. CXCL8/IL8 and CXCL1/GROα were not decreased by ASC-CM on synoviocytes but were only partially reduced on chondrocytes. Moreover, ASC-CM was less efficient both on basal inflamed OA chondrocytes and synoviocytes in reducing proteinases, such as MMP13, ADAMTS4, ADAMTS5 and increasing TIMP1 and TIMP3 compared to ASC in co-culture. The different ratios of ASC-CM contain lower amounts of PGE2 which were not sufficient to reduce inflammatory factors. Conclusions: These data show that ASC-CM has a limited ability to decrease inflammatory and proteinases factors produced by OA chondrocytes or synoviocytes. ASC-CM is not sufficient to recapitulate the beneficial effect demonstrated using ASC in co-culture with inflamed OA chondrocytes and synoviocytes and shows that their use in clinical trials is fundamental to counteract OA progression.